2019
DOI: 10.3390/atmos10120802
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Rossby Centre Regional Climate Model Rainfall Simulations over West Africa Using Large-Scale Spatial and Temporal Statistical Metrics

Abstract: Climate models are usually evaluated to understand how well the modeled data reproduce specific application-related features. In Africa, where multisource data quality is an issue, there is a need to assess climate data from a general perspective to motivate such specific types of assessment, but mostly to serve as a basis for data quality enhancement activities. In this study, we assessed the Rossby Centre Regional Climate Model (RCA4) over West Africa without targeting any application-specific feature, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The spatial patterns of ET for the historical and future climate were examined to provide a better understanding of their seasonality and quantify their relative spatial distribution in the future period (2020-2099) across the continent. We noted that the simulated ET amounts were maximum over the equatorial regions (between 5 • S and 5 • N); this is consistent with the P seasonality in West Africa [74,75] and the equatorial region [27,76]. The amount reduced moving towards the humid-tropical region, the Sahelian region, and, finally, in the arid region of the Sahara Desert (Figure 4a).…”
Section: Discussionsupporting
confidence: 80%
“…The spatial patterns of ET for the historical and future climate were examined to provide a better understanding of their seasonality and quantify their relative spatial distribution in the future period (2020-2099) across the continent. We noted that the simulated ET amounts were maximum over the equatorial regions (between 5 • S and 5 • N); this is consistent with the P seasonality in West Africa [74,75] and the equatorial region [27,76]. The amount reduced moving towards the humid-tropical region, the Sahelian region, and, finally, in the arid region of the Sahara Desert (Figure 4a).…”
Section: Discussionsupporting
confidence: 80%
“…Although most of these studies adopted direct assessment of RCMs with observations, they have been instrumental in showing the ability of RCMs to reproduce key features of the African climate system. Studies over Africa targeting and discussing the AV issue have been scarce in the literature, but a few recent studies [22][23][24][25][26] have discussed and addressed some aspects. This is particularly due to the lack of African scientists training on these emerging and robust assessment methods, but more generally owing to the variable, incomplete, and inhomogeneous availability of CORDEX phase I simulations from different modelling centers [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its overall performance is better than its predecessor ECHAM5/MPIOM model based on a modified Reichler-Kim standardized error due to improvements of the extratropical circulation [24]. RCA4 was selected as the regional climate model (RCM) because a recent study found that it can adjust the boundary conditions, resulting in a significant reduction of biases in the dynamically downscaled outputs [25]. Furthermore, many previous studies verified the credibility and advantage regarding the MPI-ESM-LR-RCA4 (GCM-RCM) chain on the projection of climate change signal over different CORDEX regions [26,27].…”
Section: Datamentioning
confidence: 99%